Risk group characteristics and viral transmission clusters in South-East Asian patients infected with HIV-1 circulating recombinant form (CRF)01_AE and subtype B - Oyomopito, Rebecca A (Kaohsiung J Med Sci, 2015)
HIV-1 epidemics in Asian countries are driven by varying exposures. The epidemiology of the regional pandemic has been changing with the spread of HIV-1 to lower-risk populations through sexual transmission. Common HIV-1 genotypes include subtype B and circulating recombinant form (CRF)01_AE. Our objective was to use HIV-1 genotypic data to better quantify local epidemics. TASER-M is a multi-centre prospective cohort of HIV-infected patients. Associations between HIV-exposure, patient gender, country of sample origin and HIV-1 genotype were evaluated by multivariate logistic regression. Phylogenetic methods were used on genotypic data to investigate transmission relationships. A total of 1086 patients from Thailand, Hong Kong, Malaysia and the Philippines were included in analyses. Proportions of males within countries varied (Thailand: 55.6%, Hong Kong: 86.1%, Malaysia: 81.4%, Philippines: 93.8%; p <0.001) as did HIV exposures (Heterosexual contact: Thailand: 85.7%, Hong Kong, 46.2%, Malaysia: 47.8%, Philippines: 25.0%; p <0.001). After adjustment, we found increased subtype B infection among men-who-have-sex with-men, relative to heterosexual-reported exposures (OR = 2.4, p <0.001). We further describe four transmission clusters of 8–15 treatment naive, predominantly symptomatic patients (two each for subtype B and CRF01_AE). Risk-group sub-populations differed with respect to the infecting HIV-1 genotype. Homosexual exposure patients had a higher odds of being infected with subtype B. Where HIV-1 genotypes circulate within countries or patient risk-groups, local monitoring of genotype-specific transmissions may play a role in focussing public health prevention strategies. Phylogenetic evaluations provide complementary information for surveillance and monitoring of viruses with high mutation rates such as HIV-1 and Ebola.